Diseño e implementación de un prototipo de plataforma tipo tijera para el monte y desmonte de cajas de velocidades de cambio para vehículos de 500 kilogramos. (2021)
In the city of Neiva, Huila, the company Autoservices lacks a mobile device to provide repair and maintenance services within the workshop and in the open field, therefore, it is limited to use the existing tools of the company. Based on the above problem, this degree work addressed the stages of design and construction of a prototype of a scissor type platform for the mounting and dismounting of gearboxes for vehicles up to 500 k g.The methodology by phases allows firstly, to carry out the study and characterization of the load lifts from the review of eight theses of degree work. Subsequently, calculations and simulation analysis were carried out using SolidWorks software and fin was built to lift a load of up to 500 kg at a maximum height of 750 mm. ally a prototype